(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article analyzes the theoretical foundations of the synergetic educational approach and reveals its role in the formation of the professional competence of future educators. The relevance of the topic, the application of the synergetic model to the pedagogical system, the role of foreign experiences, and the current state of competence development in a synergetic environment are presented on a scientific basis.